Pengaruh Pengalaman Merek, Autentisitas Merek, Ekuitas Merek, Terhadap Loyalitas Merek Melalui Kepuasan Pelanggan - Ika Widayani; Jul Aidil Fadli (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
With the rapid development of the market, the beauty industry in Indonesia is experiencing intense competition, requiring companies to devise effective strategies to build and maintain customer satisfaction. These efforts are carried out by improving the quality and benefits of the products offered, with the aim of creating long-term relationships between companies and customers. This study aims to analyze the influence of brand experience, brand authenticity, and brand equity in shaping brand loyalty mediated by customer satisfaction toward the Somethinc beauty product brand in Bekasi. The study employs a quantitative approach using purposive sampling techniques on 120 respondents who have used Somethinc products for 6 months. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the study indicate that customer satisfaction positively contributes to brand loyalty and mediates the influence of brand experience provided by the Somethinc beauty product brand. However, this study did not find an influence of brand equity in increasing customer satisfaction.